The Solutions for The Conflict of Laws Relating to Copyright and Its Exploitation" A Comparative Study" - Al-Hussien, Shaima "Moh'd Said"; Da'jeh, Asia Khalaf Mohammad Al; Alzubi, Ali Ahmad (Journal of Ecohumanism, 2024)
Determining the applicable law for copyright is a complex issue in the jurisprudence of private international law. This is because it is an intangible moral property, meaning that the nature of the subject to which the right is attributed differs from other material rights. In addition, most legislations have not established specific attribution rules for moral rights, making it difficult to determine the applicable law for copyright. Hence, the research problem is embodied in the absence of explicit and clear texts that address the issue of conflict of laws if it relates to the author’s topics moving between the scope of more than one law, which leads to an overlap in the scope of the applications of the law that related to those rights, raising the issue of which law should apply and which one is more accurate in achieving justice. The importance of this research is evident in raising the awareness among rights holders of the existence of a legal organization that protects the copyright, which may ease their minds due to their prior knowledge of the existence of a law that protects the product of their mind on the one hand and deters the aggressor on the other hand. Moreover, this study aimed to demonstrate the validity of the laws referred to by the traditional attribution rules to resolve conflicts of laws in matters related to copyright. It must be noted that the study adopted the analytical and descriptive comparative approach between Jordanian law and Iraqi law and the role of each in resolving problems arising from conflicts of laws.The study found that the Jordanian legislator specifically addressed unpublished works in Article 57 of the Copyright Protection Law, clarifying whether they fall under the law's provisions. However, we did not find an explicit provision in the Iraqi Copyright Protection Law regulating the issue of unpublished works. However, the researcher recommended that the Jordanian legislator conclude new bilateral or regional agreements in addition to joining international agreements due to the inadequacy or inappropriateness of traditional agreements related to judicial cooperation to rule on what arises from a conflict of legislative jurisdiction regarding copyright.